Extreme mountain bike challenges may induce sub-clinical myocardial damage - Ortega, F. B.; Ruiz, J. R.; Gutierrez, A.; Castillo, M. J. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The relationship between extreme exercise and coronary artery disease is not well understood, and the information available is contradictory. The aim of the present study was to determine whether strenuous endurance exercise, performed under conditions in which the partial pressure of environmental oxygen varies constantly, can induce myocardial cell injury. Methods: Plasma urea, creatinine, creatine kinase, myoglobin and cardiac troponin I (cTnI) concentrations were measured the day before and immediately after a mountain bike challenge (distance 95 km, cumulative altitude difference 2 340 m) in eleven amateur male cyclists. Results: All biochemical markers of muscle cell damage increased significantly after exercise. Although cTnI concentrations also increased significantly, they remained below the threshold (0.5 µg/L) indicative of acute myocardial infarction. Conclusions: In male, amateur mountain bikers, this kind of strenuous exercise may induce sub-clinical myocardial injury.